Izobraževanje o človekovem dostojanstvu v srednjih šolah - Kleindienst, Petra (Sodobna pedagogika, 2025)
This article presents findings on Slovenian high school students’ perceptions of the concept of human dignity and its integration into the educational process. It is based on a qualitative study that focuses on students’ understanding of human dignity, their interest in learning about this topic, and the contribution of high schools to education on human dignity. The findings show that students perceive dignity as a multifaceted concept that encompasses a sense of self-worth, respect for rights, and ethical behavior. Students’ interest in learning about human dignity is mixed; however, the majority express strong interest, particularly when the topic is introduced in a relatable and interactive way. Nevertheless, the study highlights the lack of systematic coverage of this topic within school curricula, as human dignity is often addressed only within specific subjects. The article advocates for a more comprehensive integration of education on human dignity across different school subjects, as well as the use of participatory teaching methods such as debates, project-based learning, and interactive workshops. Schools should strive to better interconnect the various dimensions of dignity within both curricular and extracurricular activities, thereby enabling students to develop a deeper understanding and practical application of this concept in an increasingly complex society. The research findings contribute to the development of innovative educational approaches and encourage policymakers and educators to strengthen the role of human dignity in the educational process.
Keywords: človekovo dostojanstvo; education; human dignity; izobraževanje; policies; politike; school; srednja šola; values; vrednote